Analisis Strategi Pemasaran pada PT. Prambanan Kencana - Willianto Willianto (Universitas Tarumanagara, 2020)
PT. Prambanan Kencana is an importer and distribution company which is founded in 1953 dan they offer quality food and beverages product. This research aims to analyze marketing strategy being used in PT. Prambanan Kencana in accordance to the internal and external factor and to seek for alternative marketing strategy in PT. Prambanan Kencana by utilizing Matriks IFE, Matriks EFE, Matriks IE, and Matriks SWOT. Method used is qualitative descriptive. The result of the research depict that PT. Prambanan Kencana has its own strength, weakness, opportunity and Threats and there are strategies to handle it. PT. Prambanan Kencana also is on the V grid in Matriks IE in which the best strategy is the hold and maintain strategy.